2014
DOI: 10.1027/1016-9040/a000183
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of Working Memory in Intellectual Functioning

Abstract: Cognitive psychology offers an important contribution to the understanding of the mechanisms underlying intelligence. In this paper, we synthesize the research showing that, among the different cognitive mechanisms associated with intelligence, working memory has a particularly high explanatory power, especially when considered in its active component involving not only the maintenance (as in short-term memory) but also the manipulation of information. The paper considers two main implications of this finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 100 publications
3
10
0
Order By: Relevance
“…There is also research indicating that digit‐span tasks, such as those included in the WISC‐IV, require a lower level of cognitive control as compared with dual tasks test (e.g., Engle, Tuholski, Laughlin, & Conway, ). This finding corroborates the idea that the digit span task requires verbal abilities and—to a latter extent—cognitive control resources (see Giofrè, Mammarella, & Cornoldi, ; and Cornoldi & Giofrè, for a review).…”
Section: Introductionsupporting
confidence: 84%
“…There is also research indicating that digit‐span tasks, such as those included in the WISC‐IV, require a lower level of cognitive control as compared with dual tasks test (e.g., Engle, Tuholski, Laughlin, & Conway, ). This finding corroborates the idea that the digit span task requires verbal abilities and—to a latter extent—cognitive control resources (see Giofrè, Mammarella, & Cornoldi, ; and Cornoldi & Giofrè, for a review).…”
Section: Introductionsupporting
confidence: 84%
“…The classical tripartite model (Baddeley & Hitch, 1974) is the most common, and is distinguished by two slave systems (verbal and visuospatial), together with a central executive component. Alternative WM models have also been proposed but will not be discussed here (see Cornoldi and Giofrè (2014) for a review). It has been suggested that cognitive control is an important factor when considering WM capacity, with a distinction between tasks requiring a lower level of cognitive control (i.e.…”
Section: Math Anxietymentioning
confidence: 99%
“…Reliance on IQ to classify SLD has sometimes been excessive, but it does seem to provide important additional information. In this study, we focused on the WISC-IV battery for two main reasons: (i) the WISC scales are the most widely used procedures for assessing intelligence in many countries (Evers et al, 2012); and (ii) the latest version of the WISC makes it possible to distinguish between different index scores and includes a measure of working memory, a variable that appears to be strongly involved in SLDs (Cornoldi & Giofrè, 2014).…”
Section: Discussionmentioning
confidence: 99%